Effect of cutting parameters on the surface roughness of titanium alloys using end milling process - Yusuf, K.; Nukman, Y.; Yusof, T.M.; Dawal, S.Z.; Yang, H.Q.; Mahlia, T.M.I.; Tamrin, K.F. (Academic Journals, 2010)
Titanium alloys have been widely used in industries, especially aerospace industries, due to their good mechanical and chemical properties. However, machining of titanium alloys involves expensive tooling cost at the expense of getting good surface roughness. This paper describes a comprehensive study of end milling of titanium alloys. The study investigated the optimum parameters that could produce significant good surface roughness whereby reducing tooling cost. It employed the Taguchi design method to optimize the surface roughness quality in a Computer Numerical Control (CNC) end mills. The control parameters were spindle speed, feed rate, depth of cut and type of end milling tool. On the other hand, the noise parameters were coolant pressure and patterns of cut. Then, an orthogonal array of L(8) (2(7)) and analysis of variance (ANOVA) were carried out to identify the significant factors affecting the surface roughness. The best parameters were then chosen based on the signal-to-noise ratio (SNR). The experimental results indicated that the most significant factors affecting the surface roughness of Titanium alloy during end milling process were primarily the spindle speed of machine, secondly, the type of end mills tool used, thirdly, the feed rate adopted and lastly, the depth of cut chosen.